Unsatisfied Reporting Quality of Clinical Trials Evaluating Immune Checkpoint Inhibitor Therapy in Cancer - Chen, Chen; Zhou, Yixin; Zhang, Xuanye; Wang, Yuhong; He, Li-na; Lin, Zuan; Chen, Tao; Jiang, Yongluo; Hong, Shaodong; Zhang, Li (Frontiers in Immunology, 2021)
Background: More and more immune-oncology trials have been conducted for treating various cancers, yet it is unclear what the reporting quality of immune-oncology trials is, and characteristics associated with higher reporting quality. Objective: To evaluate the quality of immune-oncology trials. Methods: The PubMed and Cochrane library were searched to identify all English publications of clinical trials assessing immunotherapy for cancer. Reporting quality of immune-oncology trials was evaluated by a quality score with 11-point derived from the Trial Reporting in Immuno-Oncology (TRIO) statement, which contained two parts: efficacy score with 6-point and toxicity score with 5-point. Linear regression was used to identify characteristics associated with higher score. Results: Of the 10169 studies screened, 298 immune-oncology trial reports were enrolled. The mean quality score, efficacy score and toxicity score were 6.46, 3.61 and 2.85, respectively. The most common well reported items were response evaluation criteria (96.0%) and toxicity grade (98.7%), followed by Kaplan-Meier survival analyses (80.5%). Treatment details beyond progression (12.8%) and toxicity onset time and duration (7.7%) were poorly reported. Multivariate regression revealed that higher impact factor (IF) (IF>20 vs. IF<5, P<0.001), specific tumor type (P=0.018 for lung, P=0.021 for urinary system, vs. pan cancer) and a certain kind of immune checkpoint blocking agent (P<0.001 for anti-PD-1 or multi-agents, vs. anti-CTLA-4) were independent predictors of higher quality score. Similar independent predictive characteristics were revealed for high efficacy score. Only IF > 20 had a significant high toxicity score (P<0.001). Conclusion: Immune-oncology trials presented an unsatisfied quality score, especially in the reporting of treatment details beyond progression and toxicity onset time and duration. High IF journals have better reporting quality. Future improvement of trial reporting was warranted to the benefit-risk assessment of immunotherapy.